PENGEMBANGAN BAHAN AJAR MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK SISWA KELAS V SD NEGERI KERTOSONO - Maria Luthfiana; Yufitri Yanto (LP4MK STKIP PGRI Lubuklinggau, 2021)
The aims of this research were 1) to determine designing process of developing teaching materials used the Indonesian Realistic Mathematical Approach for students grade V SDN Kertosono and 2) Produce the effective teaching materials using the Indonesian Realistic Mathematical Approach for students of SDN kertosono. This type of research is Research and Development Using the Instructional Development Model (MPI). The population of this research were all fifth grade students of SD Negeri Kertosono, there 25 students as the sample. Data collection was carried out by using interview techniques, questionnaires, and tests. The teaching material was effective based on the completeness of learning outcomes and the positive response of students. In conclusion, practical to use as seen from the expert's assessment which shows that the teaching material has very good criteria with a percentage of 82.95%. There were 22 students who showed positive responses and 3 students who showed negative responses, the student learning outcomes test showed 84% of students scored above the minimum criteria.